SYNTHESIS OF POLYELECTROLYTE COMPLEX FILMS OF CHITOSAN-ALGINATE BY ADDITION OF KELOR LEAVES EXTRACT (Moringa oleifera) FOR FOOD PACKAGING - Baiq Amelia Riyandari; Yupita Tri Rizki; M. Ramdani (Jurnal Kimia Riset, 2022)
This research aims to synthesize the polyelectrolyte complex (PEC) using chitosan and alginate as matrix film with the addition of kelor leaves extract (Moringa oleifera). The preparation of PEC films of chitosan-alginate by addition of kelor leaves extract (Moringa oleifera) had been implemented. The kelor leaves was prepared by drying process under the sun for removing water content and the dried kelor leaves was extracted using maceration technique. The final concentrations of film solution used in this study were 0.0% (Film E0), 0.50% (Film E1), 0.75% (Film E2), and 1.00% (Film E3). The PEC chitosan-alginate films with addition of kelor extract were prepared in room temperature (± 25 °C) and pH of film solution was ± 4.0. The result of film’s characterization using FTIR spectrophotometer showed that PEC films of chitosan-alginate were formed through the molecular interaction between chitosan which protonated into amine groups (–NH3+) and alginate which dissociated into carboxylate groups (–COO−). Based on FTIR spectrum, it also showed that there were some wavenumber shifts after addition of kelor leaves extract into PEC films of chitosan-alginate. It was confirmed that there were the changing of molecular interaction between PEC chitosan-alginate films due to presence of kelor extract, indicating that PEC chitosan-alginate films with kelor extract had been formed. Morphological analysis using a scanning electron microscope (SEM) displayed both porous and heterogeneous distribution on the surface after addition of kelor extract.